From immigrants to sports figures: the case study of the IOC refugee team in rio olympics 2016 - Abd Rahim, Badruel Hairiel; Mohamad Diah, Nurazzura; Aman, Mohd Salleh (International Institute of Islamic Civilisation and Malay World (ISTAC), IIUM., 2018)
This paper examines the experiences of refugee athletes in pursuing their ultimate dream to compete in the Olympics, and explores the challenges and prospects they faced. Relevant data were obtained from secondary sources, such as sports articles and biographies on websites, about refugee athletes competing in the Rio Olympics in 2016. Eleven sports personalities among the refugees from South Sudan, Syria, Democratic Republic of Congo and Ethiopia were studied. They represented the Refugee Team in judo, athletics and swimming. A summative content analysis was conducted to see variations in their sporting motives. The analysis suggests that despite of harsh living conditions in their home countries, refugees’ passion to compete in sport was very much alive when they arrived at the host countries. The paper also reveals that host countries like Germany, Brazil, and Luxembourg provided several opportunities for the refugees to venture into sport, but available opportunities are selective due to their status as refugees. Also, their participation in sport is confined to Olympic events only. Today, participation in sport is seen as an avenue for refugees to salvage their pride and dignity apart from seeking better opportunities in life. Indeed, sport is a powerful tool to unite people from different backgrounds and nationalities.